Quality criteria for studies assessing the acute effects of heading: results from a UEFA expert panel - Peek, K.; Franchi, M.; Lemmink, K.; Balsom, P.; Meyer, T. (Sports Medicine, 2024)
There is increasing concern regarding the effects of heading in football on brain health including cognitive, behavioural and neuromotor function, with research suggesting an association between repeated ball-head impacts and neurodegenerative disease. While longitudinal studies to determine the long-term consequences of heading are challenging, there have been short-term `acute` studies conducted, with some studies lacking appropriate methodology to ensure valid results. The Union of European Football Associations (UEFA) established a panel of experts to determine methodological recommendations for the conduct of studies that explore the acute effects of heading (defined as a single session of heading conducted either in a laboratory setting or following match play or a training session). The aim of this panel was to create quality criteria for acute heading studies that will form part of the eligibility assessment when applying for UEFA research funding (although the criteria can be applied to the conduct of acute heading research more widely). This process was deemed necessary to counter studies with poor methodological quality that used heading trials that did not accurately represent player exposure to ball-head impacts through football practice and match play (such as small sample sizes, unrealistically high heading exposure, and a lack of consideration of confounding variables). The panel identified core design decisions that authors should consider when designing and conducting acute heading research, with key methodological requirements for each domain pertaining to participants, heading trials, confounding variables, statistics and dependent/target variables and their measurement. After two rounds of reviews, the final list of quality criteria was agreed by the panel and will be applied to the next round of UEFA grant applications.